(untitled) (Ustozlar uchun, 2026)
Confidence plays a crucial role in second language acquisition, particularly in speaking skills. This article explores the importance of confidence in speaking English, examining its psychological, linguistic, and social dimensions. It argues that confidence significantly enhances fluency, reduces communication anxiety, and promotes effective interaction. The paper also discusses strategies for developing confidence and highlights its impact on academic and professional success.